Best Answer

9 is the constant.

5 is the coefficient of the variable term.

X is the variable term.

Q: What is the constant for 5x plus 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

'9' is the constant, because '9' u are adding 9 all the time

5x-4y+9y+x-9+7 = 5x + x - 4y + 9y - 9 + 7 = 6x + 5y - 2 ■

5x + 4 - 3x + 5 + 2x - 9 = 4x

25x2+30x+9 25*9=225 15*15=225 15+15=3025x2+15x+15x+9[5*5xx 3*5x] [3*5x 3*3]5x(5x+3)+3(5x+3)(5x+3)(5x+3)Answer: (5x+3)2

5x² - 18x + 9 = (5x² - 15x) - (3x - 9) = 5x(x - 3) - 3(x - 3) = (5x - 3)(x - 3).

Related questions

'9' is the constant, because '9' u are adding 9 all the time

It is 5x - 9.

5x = 4x + 9 x = 9

6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1

5x-4y+9y+x-9+7 = 5x + x - 4y + 9y - 9 + 7 = 6x + 5y - 2 ■

5x + 4 - 3x + 5 + 2x - 9 = 4x

If: x+9+5x = 21+2x Then: x = 3

39 = 5x + 9 5x = 39 - 9 5x = 30 x = 30 / 5 x = 6

5x+18 = 2x+9 5x-2x = 9-18 3x = -9 x = -3 and y = 3

4(5x + 3) - 9 = 20x + 3

25x2+30x+9 25*9=225 15*15=225 15+15=3025x2+15x+15x+9[5*5xx 3*5x] [3*5x 3*3]5x(5x+3)+3(5x+3)(5x+3)(5x+3)Answer: (5x+3)2

5x² - 18x + 9 = (5x² - 15x) - (3x - 9) = 5x(x - 3) - 3(x - 3) = (5x - 3)(x - 3).